Penguatan Inovasi Layanan Bimbignan dan Konseling From Pandemi to Endemic - Ar, Silvia; Putri, Rani Mega (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
This paper aims to describe the meaning of guidance and counseling service innovation, how to develop innovation, forms of innovation during the COVID-19 pandemic and endemic, identify various efforts to strengthen Guidance and Counseling services. The preparation of this article is based on a literature study that innovation is a very important thing for BK, otherwise BK will not be abandoned by students and not meaningful for students. The way BK teachers develop innovation includes the question of what improvements can be made, creating interesting and meaningful BK services, collaborating to produce innovations. Forms of innovation in the midst of a pandemic include synchronous tele-guidance and Counseling, open service materials that can be accessed by all, self-assessment tutorials, self-healing tutorials. Efforts to increase innovation in BK services through regulation, execution, and empowerment. Based on definite studies as follows; BK teachers always try to think and behave innovatively so that the services developed are attractive to them and the desired goals can be achieved, both during the pandemic and in the final period.